Investigation and analysis of mental health status of the older adult in western rural areas - Shuai Zhao; Liangfu Han; Yi Liu; Xudong Rui (Frontiers in Public Health)
BackgroundThe mental health of the older adult in western rural areas is an area of growing concern. Mental health, as defined by the World Health Organization, encompasses emotional, psychological, and social well-being, affecting how individuals think, feel, and act. In this study, we operationalize mental health through four validated dimensions: depression (emotional well-being), anxiety (psychological stability), loneliness (social connectedness), and life satisfaction (overall subjective well-being), which together provide a comprehensive assessment of mental health status. Understanding their mental health status and associated factors is crucial for developing effective interventions and improving their quality of life. While social support has been established as both a preventive and prognostic factor for mental health in various populations, its specific role and mechanisms in western rural older adult populations require further investigation. However, limited research has comprehensively explored this topic, leaving gaps in knowledge regarding the complex interplay of various influencing factors.MethodsA cross-sectional study was conducted among 1,543 older adult individuals in western rural areas. The western rural areas in this study specifically refer to rural regions in Guizhou, Yunnan, and Sichuan provinces of China, characterized by mountainous terrain, ethnic diversity (including Yi, Miao, and other minority groups), lower economic development compared to eastern regions, and unique cultural practices such as traditional community support systems and intergenerational living arrangements. A multi-stage sampling strategy was employed to obtain a representative sample. Demographic information, health-related data, and mental health status were collected through face-to-face interviews. Structured questionnaires were used to gather details on age, gender, education, marital status, household income, chronic disease status, and living arrangements. Social support was measured using the Social Support Rating Scale (SSRS), which includes three dimensions: objective support (actual received support), subjective support (perceived support), and support utilization. The total score ranges from 12–66, with higher scores indicating better social support. Scores were categorized as low (≤22), moderate (23–44), and high (≥45) based on established cut-offs. Four validated scales, namely the Geriatric Depression Scale (GDS-15), Generalized Anxiety Disorder Scale (GAD-7), UCLA Loneliness Scale, and Life Satisfaction Scale, were utilized to assess depression, anxiety, loneliness, and life satisfaction, respectively. These four scales have been extensively validated as comprehensive measures of mental health in older adult populations, with meta-analyses demonstrating their collective ability to capture 85–90% of mental health variance in older adults. Univariate analysis, multivariate logistic regression, and mediational analysis were performed to explore the relationships between different factors and mental health outcomes. To provide a comprehensive understanding of mental health burden, we also analyzed participants with multiple mental health symptoms (defined as having ≥3 of the four assessed conditions: depression, anxiety, loneliness, and low life satisfaction).ResultsOverall, 30.3% of the older adult were at risk of depression, 26.0% had anxiety symptoms, 32.5% experienced loneliness, and 40.1% were satisfied with their lives. Additionally, 18.7% of participants had multiple mental health symptoms (≥3 conditions), with this group showing significantly lower social support scores (mean 28.4 ± 7.2) compared to those with fewer symptoms (mean 38.6 ± 8.9, p < 0.001). Subgroup analysis showed that age, gender, education level, and income were significantly associated with mental health. Older adult individuals aged 70–79 and ≥80 had higher rates of depression, anxiety, and loneliness, while those aged 60–69 had a relatively higher life satisfaction. Females had higher depression and anxiety rates than males. The illiterate group had elevated rates of negative mental health outcomes, and the high-income group had a higher life satisfaction rate. Multivariate logistic regression identified age ≥70 years, female gender, illiteracy, low income (≤1,000 yuan/month), ≥3 chronic diseases, living alone, low social support, and no healthcare insurance as significant risk factors for depression. Similar patterns were observed for the multiple mental health symptoms group, with low social support showing the strongest association (AOR = 3.42, 95% CI: 2.51–4.66, p < 0.001). Marital status (widowed), religious engagement, and employment status did not significantly influence depression. Mediational analysis, conducted using the Baron and Kenny approach and Sobel test, revealed that social support played a crucial mediating role in the relationship between some factors and depression. Notably, the mediating effects of social support in western rural areas were significantly stronger than those reported in eastern rural areas (indirect effect 0.60 vs. 0.35 for chronic diseases, p < 0.01), suggesting that the mountainous geography and dispersed settlement patterns in western regions amplify the importance of social networks for mental health maintenance. The indirect effects were calculated as the product of the coefficients for the path from the independent variable to the mediator and from the mediator to the outcome, with statistical significance tested using bootstrapping methods (1,000 iterations).ConclusionThe mental health status of the older adult in western rural areas varies significantly among different subgroups. Multiple factors are associated with their mental health, and social support has a mediating effect. The unique geographical isolation and cultural context of western rural areas create distinct mental health challenges that differ from other rural regions in China, requiring culturally-adapted, community-based interventions that leverage traditional support systems while addressing modern healthcare access barriers. Our findings align with the broader health promotion literature while providing specific insights for this population. Community-based interventions, such as community therapy groups, peer support networks, and culturally adapted social engagement programs, should be prioritized to enhance social support and improve mental health outcomes. These findings provide important insights for the development of targeted mental health interventions and policies to enhance the well-being of this vulnerable population.